Secondary battery and electric device
By using a second negative electrode active material including primary particles and secondary particle carbon materials in the upper region of the negative electrode film layer, the problem of insufficient fast charging performance of secondary batteries under low temperature conditions is solved, and a higher low-temperature fast charging performance and energy density are achieved.
Patent Information
- Application Number
- CN202410338654.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-03-22
AI Technical Summary
The existing secondary batteries have insufficient fast charging performance under low temperature conditions, making it difficult to meet the high requirements of users for charging capabilities.
A second negative electrode active material including carbon material of primary particles and carbon material of secondary particles is provided in the upper region of the negative electrode film layer. By optimizing the volume distribution particle size and powder OI value of the carbon material, the low-temperature fast charging performance of the battery is improved.
By optimizing the composition of the negative electrode film layer, the fast charging performance of the secondary battery under low temperature conditions is significantly improved, while taking into account the energy density and circulation performance of the battery.
Smart Images

Figure BDA0004756359300000201 
Figure BDA0004756359300000202 
Figure BDA0004756359300000211
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to secondary batteries and electrical devices. Background Art
[0002] In recent years, with the development of secondary battery technology, it has been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] Because of the widespread use of secondary batteries, users have also put forward higher requirements on the charging capacity of secondary batteries. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery with improved low-temperature fast charging performance and an electrical device using the secondary battery.
[0005] In order to achieve the above object, the first aspect of the present application provides a secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector; the negative electrode film layer comprises a lower region and an upper region, the lower region comprises a first negative electrode active material, and the upper region comprises a second negative electrode active material; wherein the second negative electrode active material comprises a primary particle carbon material and a secondary particle carbon material at the same time, and the volume distribution particle size D of the second negative electrode active material is V 50 is less than or equal to 13μm.
[0006] The above technical solution is used in combination by setting two carbon materials (i.e., primary particle carbon material and secondary particle carbon material) in the negative electrode film layer area (i.e., upper area) away from the negative electrode current collector, wherein the granulation structure of the secondary particle carbon material is conducive to reducing the OI value of the material, thereby facilitating low-temperature fast charging performance, while the single particle carbon material (i.e., primary particle) is conducive to increasing the active specific surface area, reducing the charge transfer resistance (Rct), and further improving the low-temperature fast charging performance of the battery. In addition, by matching different particle carbon materials, the volume distribution particle size D of the second negative electrode active material is V 50 is less than or equal to 13μm, so that the upper area of the electrode has a better pore distribution state, which is beneficial to improving the transmission performance of ions and electrons and further improving the low-temperature fast charging performance of the battery.
[0007] In some embodiments, the volume distribution particle size D of the second negative electrode active material is V 50 is 8 μm to 13 μm. The volume distribution particle size D of the second negative electrode active material V50 Within the above range, it is more conducive to forming a better pore distribution state in the upper area of the electrode, which is more conducive to improving the transmission performance of ions and electrons and improving the low-temperature fast charging performance of the battery.
[0008] In some embodiments, the volume distribution particle size D of the carbon material of the primary particles is V 50 is smaller than the volume distribution particle size D of the carbon material of the secondary particles V 50; Optionally, the volume distribution particle size D of the carbon material of the primary particles V 50 is 3.5 μm to 6 μm, and more preferably 3.5 μm to 5.0 μm; Optionally, the volume distribution particle size D of the carbon material of the secondary particles V 50 is 10.0 μm to 14.0 μm, and more preferably 10.0 μm to 13.5 μm.
[0009] The above technical solution includes a carbon material with smaller primary particles + a carbon material with larger secondary particles in the negative electrode film layer area away from the negative electrode current collector, wherein the granulation structure in the secondary particle structure with larger particle size is more conducive to reducing the OI value of the material, which is beneficial to the low-temperature fast charging performance; the carbon material with mixed small primary particles is more conducive to maintaining a higher active specific surface area, further improving the low-temperature fast charging performance of the battery.
[0010] In some embodiments, the powder OI value of the carbon material of the primary particles is greater than the powder OI value of the carbon material of the secondary particles; optionally, the powder OI value of the carbon material of the primary particles is 3 to 6; optionally, the powder OI value of the carbon material of the secondary particles is 2 to 5.
[0011] In the above technical solution, the powder OI value of the carbon material of the primary particles is greater than the powder OI value of the carbon material of the secondary particles, which is conducive to the rapid deintercalation of ions. In addition, by keeping the powder OI values of the two carbon materials within the above range, the material has ion embedding ports in all directions, thereby being able to quickly receive ions, thereby further improving the low-temperature fast charging performance of the secondary battery.
[0012] In some embodiments, the specific surface area of the carbon material of the primary particles is greater than the specific surface area of the carbon material of the secondary particles; optionally, the specific surface area of the carbon material of the primary particles is 2.0 m 2 / g to 3.5m 2 / g, 2.0m can be selected 2 / g to 3.2m 2 / g; Optionally, the specific surface area of the carbon material of the secondary particles is 0.6m 2 / g to 1.5m 2 / g, optional 0.6m 2 / g to 1.2m 2 / g.
[0013] In the above technical solution, the specific surface area of the carbon material of the primary particles is greater than the specific surface area of the carbon material of the secondary particles, which is beneficial to increase the proportion of active specific surface area, improve the low-temperature fast charging performance of the battery, and reduce side reactions, thereby enabling the battery to have both good fast charging performance and cycle performance. Furthermore, when the specific surface area of the carbon material is within the corresponding above range, the ion embedding channel in the upper region of the membrane layer can be increased, promoting the rapid diffusion of ions from the surface of the particles to the bulk phase.
[0014] In some embodiments, the carbon material of the primary particles satisfies: the volume distribution particle size D of the carbon material of the primary particles V 10 is 1.0 μm to 3.0 μm.
[0015] In some embodiments, the carbon material of the primary particles satisfies: the volume distribution particle size D of the carbon material of the primary particles V 90 is 9μm to 12μm.
[0016] When the volume distribution particle size Dv10 and / or Dv90 of the carbon material of the primary particles is within the above range, it is beneficial to improve the transmission performance of ions and electrons, thereby further improving the fast charging performance of the secondary battery.
[0017] In some embodiments, the carbon material of the primary particles satisfies: the particle size distribution (D V 90-D V 10) / DV50 is 1.1 to 1.8.
[0018] The particle size distribution of the primary carbon material (D V 90-D V 10) / D V 50 Within this range, it indicates that the good distribution of the carbon material of the primary particles is beneficial to the upper region of the negative electrode film layer having a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and further improving the fast charging performance of the secondary battery.
[0019] In some embodiments, the carbon material of the primary particles satisfies: the tap density of the carbon material of the primary particles is 0.8 g / cm 3 Up to 1.1g / cm 3 When the tap density is within the above range, the compaction density of the negative electrode film layer can be increased, thereby achieving low-temperature fast charging performance while taking into account the energy density of the battery.
[0020] In some embodiments, the carbon material of the primary particles satisfies: the powder compaction density of the carbon material of the primary particles at 20000N is 1.35g / cm 3 Up to 1.55g / cm 3 When the compaction density of the powder is within the above range, the compaction density of the negative electrode film layer can be increased, thereby achieving low-temperature fast charging performance while taking into account the energy density of the battery.
[0021] In some embodiments, the carbon material of the primary particles satisfies: the graphitization degree of the carbon material of the primary particles is 90% to 93%. When the graphitization degree of the carbon material of the primary particles is within the above range, it is beneficial to improve the ion transport performance of the negative electrode film layer, so that the secondary battery can have both high energy density and good fast charging performance.
[0022] In some embodiments, the carbon material of the secondary particles satisfies: the volume distribution particle size D of the carbon material of the secondary particles V 10 is 4.5μm to 8.0μm.
[0023] In some embodiments, the carbon material of the secondary particles satisfies: the volume distribution particle size D of the carbon material of the secondary particles V 90 is 18μm to 24μm.
[0024] Volume distribution particle size D of secondary particles of carbon material V 10 and / or D V Within this range, the carbon material of the secondary particles and the carbon material of the primary particles are beneficial to the mutual matching, which is beneficial to the compaction density and further contributes to the energy density of the battery.
[0025] In some embodiments, the carbon material of the secondary particles satisfies: the particle size distribution (D V 90-D V 10) / D V 50 is 0.9 to 1.3. The particle size distribution (D V 90-D V 10) / D V 50 Within this range, it indicates that the good distribution of carbon materials is conducive to the upper region of the negative electrode film layer having a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and further improving the fast charging performance of the secondary battery.
[0026] In some embodiments, the carbon material of the secondary particles satisfies: the tap density of the carbon material of the secondary particles is 0.9 g / cm 3 Up to 1.2g / cm 3When the tap density is within the above range, it can cooperate well with the carbon material of the primary particles to increase the compaction density of the negative electrode film layer, thereby improving the low-temperature fast charging performance while taking into account the energy density of the battery.
[0027] In some embodiments, the carbon material of the secondary particles satisfies: the powder compaction density of the carbon material of the secondary particles at 20000N is 1.55g / cm 3 Up to 1.70g / cm 3 When the compaction density of the carbon material powder of the secondary particles is within the above range, it can cooperate well with the carbon material of the primary particles to increase the compaction density of the negative electrode film layer, thereby improving the low-temperature fast charging performance while taking into account the energy density of the battery.
[0028] In some embodiments, the carbon material of the secondary particles satisfies: the graphitization degree of the carbon material of the secondary particles is 92% to 95%. This is beneficial for the secondary battery to have both high energy density and good fast charging performance.
[0029] In some embodiments, based on the total mass of the second negative electrode active material, the mass proportion of the carbon material of the primary particles is less than the mass proportion of the carbon material of the secondary particles; optionally, based on the total mass of the second negative electrode active material, the mass proportion of the carbon material of the primary particles is 20% to 40%; optionally, based on the total mass of the second negative electrode active material, the mass proportion of the carbon material of the secondary particles is 60% to 80%.
[0030] By setting the mass proportion of the carbon material of the primary particles to be smaller than the mass proportion of the carbon material of the secondary particles, it is beneficial to improve the low-temperature fast charging performance of the battery while taking into account the energy density.
[0031] In some embodiments, the carbon material of the primary particles and / or the carbon material of the secondary particles is artificial graphite.
[0032] In some embodiments, the first negative electrode active material includes artificial graphite and / or natural graphite; optionally, the first negative electrode active material includes both artificial graphite and natural graphite.
[0033] In some embodiments, the first negative electrode active material includes natural graphite, and the volume distribution particle size DV50 of the natural graphite is 9 μm to 20 μm. The first negative electrode active material includes natural graphite, wherein the abundant coating layer on the surface of the natural graphite and the internal pore structure are further beneficial to the low-temperature fast charging performance.
[0034] In some embodiments, the first negative active material includes secondary particles of artificial graphite.
[0035] In some embodiments, the first negative electrode active material includes artificial graphite, and the volume distribution particle size D of the artificial graphite is V 50 is 12μm to 17μm, and can be optionally 13μm to 16μm.
[0036] In some embodiments, the first negative electrode active material comprises natural graphite. In some embodiments, the volume distribution particle size D of the natural graphite is V 10 is 5.0 μm to 12.0 μm. In some embodiments, the volume distribution particle size D of the natural graphite V 90 is 20 μm to 30 μm. In some embodiments, the particle size distribution (D V 90-D V 10) / D V 50 is 0.9 to 1.3. In some embodiments, the tap density of the natural graphite is 0.9 g / cm 3 Up to 1.2g / cm 3 In some embodiments, the natural graphite has a powder compaction density of 1.60 g / cm at 20,000 N. 3 Up to 1.90g / cm 3 In some embodiments, the degree of graphitization of the natural graphite is 96% to 98%.
[0037] In some embodiments, the first negative electrode active material comprises artificial graphite. In some embodiments, the volume distribution particle size D of the artificial graphite is V 10 is 4 μm to 8 μm. In some embodiments, the volume distribution particle size D of the artificial graphite V 90 is 25 μm to 40 μm. In some embodiments, the particle size distribution (D V 90-D V 10) / D V 50 is 1.0 to 1.4. In some embodiments, the tap density of the artificial graphite is 0.95 g / cm 3 Up to 1.25g / cm 3 In some embodiments, the powder compaction density of the artificial graphite at 20000N is 1.70g / cm 3 Up to 1.90g / cm 3 In some embodiments, the degree of graphitization of the artificial graphite is 93% to 95%.
[0038] The second aspect of the present application further provides an electrical device, comprising the secondary battery of the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0040] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0041] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0042] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0043] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0044] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0045] Description of reference numerals:
[0046] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0047] The following detailed description specifically discloses the implementation methods of the secondary battery and the electrical device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0048] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0049] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0050] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0051] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0052] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0053] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0054] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0055] In the present application, the terms "primary particles" and "secondary particles" have well-known meanings in the art. Primary particles refer to non-agglomerated particles. Secondary particles refer to agglomerated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be distinguished by using scanning electron microscopy (SEM) images.
[0056] In this application, the volume distribution particle sizes "Dv10", "Dv50" and "Dv90" involved in the reference to materials have well-known meanings in the art, which respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the materials reaching 10%, 50% and 90%, and can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0057] In the present application, the term "powder OI value" has a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray powder diffractometer (X'pert PRO) can be used for testing. The test can refer to JIS K0131-1996 and JB / T 4220-2011 to obtain the X-ray diffraction pattern of the powder sample, and the powder OI value of the sample is calculated according to OI value = I004 / I110. Among them, I004 is the integral area of the diffraction peak of the 004 crystal plane of crystalline carbon in the powder sample, and I110 is the integral area of the diffraction peak of the 110 crystal plane of crystalline carbon in the powder sample. In the X-ray diffraction analysis test of the present application, a copper target can be used as an anode target, CuKα rays can be used as a radiation source, the ray wavelength scans the 2θ angle range of 20° to 80°, and the scanning rate is 4° / min.
[0058] In this application, the term "specific surface area" has a well-known meaning in the art and can be measured by instruments and methods well-known in the art. For example, the specific surface area of solid substances can be measured by the gas adsorption BET method GB / T 19587-2004 standard, and the specific surface area analysis test method of nitrogen adsorption can be used for testing, and the specific surface area analysis test can be calculated by the BET (Brunauer Emmett Teller) method, wherein the specific surface area analysis test of nitrogen adsorption can be performed by the Tri Star II3020 specific surface and pore analyzer of Micromeritics, USA.
[0059] In this application, the "tap density" involved in the reference to materials has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, GB / T5162-2006 can be referred to and a powder tap density tester can be used for measurement. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.
[0060] In this application, the "powder compaction density" mentioned in the material has a well-known meaning in the art and can be measured by instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (for example, UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. The exemplary test method is as follows: weigh 1g of sample powder and add a bottom area of 1.327cm 2 The mold is pressurized to the required pressure, maintained for 30 seconds, released, maintained for 10 seconds, and then the powder compaction density of the material under the required pressure is recorded and calculated.
[0061] In the present application, the term "graphitization degree" has a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d002 of the C(002) crystal plane in the material crystal structure, and then calculated according to the formula g=(0.344-d002) / (0.344-0.3354)×100%. Wherein, d002 is the average interlayer spacing of the C(002) crystal plane in the material crystal structure expressed in nanometers (nm).
[0062] For systems with higher energy density requirements, thick coating is usually used, and the electrode compaction density is required to be high, which will hinder ion transmission and adversely affect the low-temperature fast charging performance of secondary batteries. Therefore, how to make high-energy-density batteries have good low-temperature fast charging performance is a technical problem that needs to be solved urgently.
[0063] The negative electrode is an important component of the secondary battery, and its performance is crucial to the performance of the secondary battery.
[0064] In view of this, the inventors cleverly improved the composition of the negative electrode film layer, which enables the secondary battery to have both high energy density and good low-temperature fast charging performance.
[0065] Based on this, the present application proposes a secondary battery.
[0066] The term “secondary battery” mentioned herein refers to a battery cell, a battery module or a battery pack.
[0067] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0068] The secondary battery provided in the first aspect of the present application includes the negative electrode sheet described below.
[0069] [Negative electrode]
[0070] The negative electrode plate of the present application includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector; the negative electrode film layer includes a lower region and an upper region, the lower region includes a first negative electrode active material, and the upper region includes a second negative electrode active material; wherein the second negative electrode active material includes both primary particle carbon material and secondary particle carbon material, and the volume distribution particle size DV50 of the second negative electrode active material is less than or equal to 13 μm.
[0071] The above technical solution is used in combination by setting two carbon materials (i.e., primary particle carbon material and secondary particle carbon material) in the negative electrode film layer area (i.e., upper area) away from the negative electrode current collector, wherein the granulation structure of the secondary particle carbon material is conducive to reducing the OI value of the material and is conducive to low-temperature fast charging performance. At the same time, the single particle carbon material (i.e., primary particle) is conducive to increasing the active specific surface area, reducing the charge transfer resistance (Rct), and further improving the low-temperature fast charging performance of the battery. In addition, by matching different particle carbon materials, the volume distribution particle size D of the second negative electrode active material is V 50 is less than or equal to 13μm, so that the upper area of the electrode has a better pore distribution state, which is beneficial to improving the transmission performance of ions and electrons and further improving the low-temperature fast charging performance.
[0072] In some embodiments, the volume distribution particle size D of the second negative electrode active material is V 50 is 8 μm to 13 μm. The volume distribution particle size D of the second negative electrode active material V 50 Within the above range, it is more conducive to forming a better pore distribution state in the upper area of the electrode, which is more conducive to improving the transmission performance of ions and electrons and improving the low-temperature fast charging performance of the battery.
[0073] In some embodiments, the volume distribution particle size D of the carbon material of the primary particles is V50 is smaller than the volume distribution particle size D of the carbon material of the secondary particles V 50. The above technical solution includes a carbon material with a smaller primary particle size and a carbon material with a larger secondary particle size in the negative electrode film layer region away from the negative electrode current collector, wherein the granulation structure in the secondary particle structure with a larger particle size is more conducive to reducing the OI value of the material, which is beneficial to the low-temperature fast charging performance; at the same time, the carbon material with a mixed primary particle size is more conducive to the active specific surface area, further improving the low-temperature fast charging performance of the battery.
[0074] In some embodiments, the volume distribution particle size D of the carbon material of the primary particles is V In some embodiments, the volume distribution particle size D of the carbon material of the primary particles is 3.5 μm to 6 μm. V 50 is 3.5 μm to 5.0 μm. In some embodiments, the volume distribution particle size D of the carbon material of the secondary particles is V 50 is 10.0 μm to 14.0 μm. In some embodiments, the volume distribution particle size D of the carbon material of the secondary particles V 50 is 10.0 μm to 13.5 μm. Through the selection and matching of the reasonable particle sizes of the primary and secondary carbon materials, the upper area of the membrane layer has good pores, ensuring the lithium ion transmission channel and further improving the low-temperature fast charging performance.
[0075] In some embodiments, the powder OI value of the carbon material of the primary particles is greater than the powder OI value of the carbon material of the secondary particles. In some embodiments, the powder OI value of the carbon material of the primary particles is 3 to 6. In some embodiments, the powder OI value of the carbon material of the secondary particles is 2 to 5.
[0076] Through the above design, the material particles have ion embedding ports in all directions, so that they can quickly receive ions from the positive electrode, thereby further improving the low-temperature fast charging performance of the secondary battery.
[0077] In some embodiments, the specific surface area of the carbon material of the primary particles is greater than the specific surface area of the carbon material of the secondary particles. By making the specific surface area of the carbon material of the primary particles greater than the specific surface area of the carbon material of the secondary particles, it is more conducive to maintaining the proportion of the active specific surface area in the upper region of the membrane layer, thereby improving the low-temperature fast charging performance of the battery.
[0078] In some embodiments, the specific surface area of the carbon material of the primary particles is 2.0 m 2 / g to 3.5m 2 In some embodiments, the specific surface area of the carbon material of the primary particles is 2.0 m 2 / g to 3.2m2 In some embodiments, the specific surface area of the carbon material of the secondary particles is 0.6 m 2 / g to 1.5m 2 In some embodiments, the specific surface area of the carbon material of the secondary particles can be 0.6 m 2 / g to 1.2m 2 Therefore, when the specific surface area of the carbon material is within the above range, the ion embedding channel in the upper region of the membrane layer can be maintained, and the ions can be rapidly diffused from the particle surface to the bulk phase.
[0079] In some embodiments, the carbon material of the primary particles satisfies: the volume distribution particle size D of the carbon material of the primary particles V 10 is 1.0 μm to 3.0 μm. When the volume distribution particle size Dv10 of the primary particles of the carbon material is within the above range, it is beneficial to improve the transmission performance of ions and electrons, thereby further improving the fast charging performance of the secondary battery.
[0080] In some embodiments, the carbon material of the primary particles satisfies: the volume distribution particle size D of the carbon material of the primary particles V When the volume distribution particle size Dv90 of the primary particles of the carbon material is within the above range, the consistency of the particles is good, which is beneficial to improving the transmission performance of ions and electrons.
[0081] In some embodiments, the carbon material of the primary particles satisfies: the particle size distribution (D V 90-D V 10) / D V 50 is 1.1 to 1.8. The particle size distribution of the primary particle carbon material (D V 90-D V 10) / D V 50 Within this range, it indicates that the good distribution of carbon materials is conducive to the upper region of the negative electrode film layer having a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and further improving the fast charging performance of the secondary battery.
[0082] In some embodiments, the carbon material of the primary particles satisfies: the tap density of the carbon material of the primary particles is 0.8 g / cm 3 Up to 1.1g / cm 3 When the tap density is within the above range, the compaction density of the negative electrode film layer can be increased, thereby achieving low-temperature fast charging performance while taking into account the energy density of the battery.
[0083] In some embodiments, the carbon material of the primary particles satisfies: the powder compaction density of the carbon material of the primary particles at 20000N is 1.35g / cm 3 Up to 1.55g / cm 3 When the compaction density of the powder is within the above range, the compaction density of the negative electrode film layer can be increased, thereby achieving low-temperature fast charging performance while taking into account the energy density of the battery.
[0084] In some embodiments, the carbon material of the primary particles satisfies: the graphitization degree of the carbon material of the primary particles is 90% to 93%. When the graphitization degree of the carbon material of the primary particles is within the above range, it is beneficial to improve the ion transport performance of the negative electrode film layer, so that the secondary battery can have both high energy density and good fast charging performance.
[0085] In some embodiments, the carbon material of the secondary particles satisfies: the volume distribution particle size D of the carbon material of the secondary particles V 10 is 4.5 μm to 8.0 μm. Volume distribution particle size D of the secondary particle carbon material V 10 Within this range, it is beneficial to the matching of the carbon material with the carbon material of the primary particles, which is beneficial to the compaction density and further contributes to the energy density of the battery.
[0086] In some embodiments, the carbon material of the secondary particles satisfies: the volume distribution particle size D of the carbon material of the secondary particles V 90 is 18μm to 24μm.
[0087] In some embodiments, the carbon material of the secondary particles satisfies: the particle size distribution (D V 90-D V 10) / D V 50 is 0.9 to 1.3. The particle size distribution (D V 90-D V 10) / D V 50 In this range, it indicates that the carbon material is well distributed, which is conducive to the upper region of the negative electrode film layer having a suitable pore structure, thereby reducing the difficulty of ion liquid phase transmission and further improving the fast charging performance of the secondary battery.
[0088] In some embodiments, the carbon material of the secondary particles satisfies: the tap density of the carbon material of the secondary particles is 0.9 g / cm 3 Up to 1.2g / cm 3 When the tap density is within the above range, it can cooperate well with the primary particles to improve the compaction density of the negative electrode film layer, thereby achieving low-temperature fast charging performance while taking into account the energy density of the battery.
[0089] In some embodiments, the carbon material of the secondary particles satisfies: the powder compaction density of the carbon material of the secondary particles at 20000N is 1.55g / cm 3 Up to 1.70g / cm 3 When the compaction density of the carbon material powder of the secondary particles is within the above range, it can cooperate well with the primary particles to improve the compaction density of the negative electrode film layer, thereby achieving low-temperature fast charging performance while taking into account the energy density of the battery.
[0090] In some embodiments, the carbon material of the secondary particles satisfies: the graphitization degree of the carbon material of the secondary particles is 92% to 95%. This is beneficial for the secondary battery to have both high energy density and good fast charging performance.
[0091] In some embodiments, based on the total mass of the second negative electrode active material, the mass proportion of the carbon material of the primary particles is less than the mass proportion of the carbon material of the secondary particles; optionally, based on the total mass of the second negative electrode active material, the mass proportion of the carbon material of the primary particles is 20% to 40%; optionally, based on the total mass of the second negative electrode active material, the mass proportion of the carbon material of the secondary particles is 60% to 80%.
[0092] By setting the mass proportion of the carbon material of the primary particles to be smaller than the mass proportion of the carbon material of the secondary particles, it is beneficial to improve the low-temperature fast charging performance of the battery while taking into account the energy density.
[0093] In some embodiments, the carbon material of the primary particles and / or the carbon material of the secondary particles is artificial graphite.
[0094] In some embodiments, the first negative electrode active material includes artificial graphite and / or natural graphite; optionally, the first negative electrode active material includes both artificial graphite and natural graphite.
[0095] In some embodiments, the first negative electrode active material comprises natural graphite, and the volume distribution particle size D of the natural graphite is V 50 is 9 μm to 20 μm. The first negative electrode active material includes natural graphite, wherein the abundant coating layer on the surface of the natural graphite and the internal pore structure are further beneficial to the low-temperature fast charging performance, and the gram capacity of the natural graphite in the lower region is higher than the capacity of the carbon material in the upper region, which is beneficial to take into account the requirements of energy density.
[0096] In some embodiments, the first negative active material includes secondary particles of artificial graphite.
[0097] In some embodiments, the first negative electrode active material includes artificial graphite, and the volume distribution particle size D of the artificial graphite isV 50 is 12μm to 17μm, and can be optionally 13μm to 16μm.
[0098] In some embodiments, the first negative electrode active material comprises natural graphite. In some embodiments, the volume distribution particle size D of the natural graphite is V 10 is 5.0 μm to 12.0 μm. In some embodiments, the volume distribution particle size D of the natural graphite V 90 is 20 μm to 30 μm. In some embodiments, the particle size distribution (D V 90-D V 10) / D V 50 is 0.9 to 1.3. In some embodiments, the tap density of the natural graphite is 0.9 g / cm 3 Up to 1.2g / cm 3 In some embodiments, the natural graphite has a powder compaction density of 1.60 g / cm at 20,000 N. 3 Up to 1.90g / cm 3 In some embodiments, the degree of graphitization of the natural graphite is 96% to 98%.
[0099] In some embodiments, the first negative electrode active material comprises artificial graphite. In some embodiments, the volume distribution particle size D of the artificial graphite is V 10 is 4 μm to 8 μm. In some embodiments, the volume distribution particle size D of the artificial graphite V 90 is 25 μm to 40 μm. In some embodiments, the particle size distribution (D V 90-D V 10) / D V 50 is 1.0 to 1.4. In some embodiments, the tap density of the artificial graphite is 0.95 g / cm 3 Up to 1.25g / cm 3 In some embodiments, the powder compaction density of the artificial graphite at 20000N is 1.70g / cm 3 Up to 1.90g / cm 3 In some embodiments, the degree of graphitization of the artificial graphite is 93% to 95%.
[0100] It should be noted that the various parameter tests on the first negative electrode active material, the second negative electrode active material or the negative electrode film layer can be performed by sampling and testing from the prepared secondary battery according to the following steps.
[0101] Discharge the secondary battery (for safety reasons, the secondary battery is generally in a fully discharged state); disassemble the secondary battery, take out the negative electrode plate, and soak the negative electrode plate in dimethyl carbonate for a certain period of time (for example, 2 hours to 10 hours); then take out the negative electrode plate, and dry it at a certain temperature and time (for example, 60°C, more than 4 hours); then take out the negative electrode plate.
[0102] Subsequently, the dried negative electrode sheet is baked at a certain temperature and time (for example, 400°C, more than 2h), and an area of the baked negative electrode sheet is selected, and the powder scraped off the upper 1 / 3 thickness film layer is used as the second negative electrode active material, and the powder scraped off the 1 / 3H film layer close to the copper foil is used as the first negative electrode active material; the collected first negative electrode active material and second negative electrode active material are sieved respectively, and finally the first negative electrode active material and second negative electrode active material samples that can be used to test the above-mentioned material parameters of this application are obtained.
[0103] As an example, the test method for the volume distribution particle size Dv50 of the second negative electrode active material can be: disperse the sample in a suitable liquid (for example, deionized water) or gas at a suitable concentration by ultrasonic treatment, etc., and use a laser particle size analyzer (such as Malvern Master Size 3000) to measure: let the sample pass through a monochromatic light beam (usually a laser), and when the light encounters the particles, it scatters at different angles, and the scattered light is measured by a multi-element detector, and these values related to the scattering pattern are stored and used for subsequent analysis. Through appropriate optical models and mathematical processes, these quantitative scattering data are converted to obtain the percentage of the particle volume on a series of discrete particle size segments relative to the total volume of the particles, thereby obtaining the particle size volume distribution. Among them, the Dv50 particle size represents the particle size corresponding to the cumulative volume distribution percentage of the particles reaching 50% from the small particle size side in the particle size distribution.
[0104] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0105] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0106] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0107] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0108] [Method for preparing negative electrode sheet]
[0109] The present application also provides a method for preparing the negative electrode sheet of the present application. The method comprises the following steps:
[0110] A first slurry containing a first negative electrode active material and a second slurry containing a second negative electrode active material are provided; the first slurry is coated on a negative electrode current collector, and then the second slurry is coated, followed by drying and cold pressing to obtain a negative electrode sheet.
[0111] In some embodiments, the first negative electrode active material, as well as an optional conductive agent, an optional binder, and other optional auxiliary agents may be dispersed in a solvent (eg, NMP) to form a first slurry.
[0112] In some embodiments, the second active material and optional conductive agent, optional binder and other optional auxiliary agents may be dispersed in a solvent (eg, NMP) to form a second slurry, wherein the second negative electrode active material includes both primary particles of carbon material and secondary particles of carbon material.
[0113] The first slurry and the second slurry can be applied at the same time or in two times. In some embodiments, the first slurry and the second slurry are applied at the same time. Applying at the same time can reduce the negative electrode film resistance, thereby further improving the rate performance and cycle performance of the secondary battery.
[0114] The coating weight of the first slurry and the second slurry can be adjusted according to actual conditions.
[0115] The first negative electrode active material, the second negative electrode active material, etc. mentioned above can be obtained by commercial purchase, or prepared by the following method of the present application.
[0116] In some embodiments, the primary particle carbon material can be prepared by the following method: crushing and shaping the coke raw material, and then graphitizing it to obtain the primary particle carbon material. Specific examples of the coke raw material may include one or more of petroleum coke, needle coke, asphalt coke and metallurgical coke. The graphitization temperature may be between 2800°C and 3200°C.
[0117] In some embodiments, the carbon material of the secondary particles can be prepared by the following method: crushing and shaping the coke raw material, mixing it with a binder for granulation, and then graphitizing it to obtain a carbon-based material containing secondary particles. Specific examples of coke raw materials may include one or more of petroleum coke, needle coke, asphalt coke and metallurgical coke. The graphitization temperature may be between 2800°C and 3200°C. Specific examples of binders may include asphalt.
[0118] The above preparation process does not include the step of forming a carbon coating layer on the surface of the material. As an example, the carbon coating layer on the surface of the carbon material can be formed by carbonizing an organic carbon source, and the organic carbon source can be a carbon-containing material suitable for coating known in the art, for example, it can include one or more of coal tar, petroleum asphalt, phenolic resin, coconut shell, etc.
[0119] [Positive electrode]
[0120] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0121] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0122] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0123] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0124] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0125] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0126] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0127] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0128] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0129] [Electrolytes]
[0130] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.
[0131] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0132] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0133] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0134] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0135] [Isolation film]
[0136] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0137] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0138] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0139] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0140] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0141] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0142] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0143] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0144] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0145] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0146] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0147] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0148] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0149] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0150] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0151] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0152] Example
[0153] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0154] Example 1
[0155] A mixed material 1-1 of the first negative electrode active material artificial graphite and natural graphite (relevant parameters are detailed in Table 1, and the mass ratio of the two is 6:4), a conductive agent Super P, a thickener CMC, and a binder SBR are mixed in a mass ratio of 96.4:1:1.2:1.4, and deionized water is added as a solvent. The mixture is stirred under the action of a vacuum stirrer until the system is uniform to obtain a first slurry.
[0156] The mixed material 2-1 of the artificial graphite of the primary particles of the second negative electrode active material and the artificial graphite of the secondary particles (relevant parameters are shown in Table 2), the conductive agent Super P, the thickener CMC, and the binder SBR are mixed in a mass ratio of 96.4:1:1.2:1.4, and the solvent deionized water is added, and the mixture is stirred under the action of a vacuum stirrer until the system is uniform to obtain a second slurry.
[0157] The first slurry is evenly coated on the negative electrode current collector copper foil. After drying, the second slurry is coated on the surface of the first slurry, and the negative electrode sheet is obtained after drying and cold pressing. The coating weights of the lower area formed by the first slurry and the upper area formed by the second slurry are "7.6mg / cm 2 ” and “5.1mg / cm 2 ", the thickness of the negative electrode single-layer film (i.e. the thickness of the film coated on one side + the thickness of the copper foil) is 0.077mm.
[0158] LiFePO4, conductive agent Super P, and binder polyvinylidene fluoride were mixed in a mass ratio of (97.4:0.8:1.8), and solvent NMP was added and stirred evenly to obtain positive electrode slurry. The positive electrode slurry was coated on the positive electrode current collector aluminum foil, and after drying and cold pressing, the positive electrode sheet was obtained.
[0159] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a solvent, and then LiPF6 is dissolved in the above solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0160] A polypropylene film (12 um thick) is used as an isolation film, and is placed in order with the positive electrode sheet and the negative electrode sheet prepared as above, so that the isolation film is located between the positive electrode sheet and the negative electrode sheet to play an isolation role, and then the electrode assembly is wound; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, formation, aging and other processes.
[0161] Embodiment 2-9
[0162] A secondary battery was assembled in the same manner as in Example 1, except that the first negative electrode active material and the second negative electrode active material shown in Table 3 were used.
[0163] Comparative Example 1
[0164] A secondary battery was assembled in the same manner as in Example 1, except that the mixture material 2-8 (Dv50 greater than 13 μm) was used as the second negative electrode active material (see Table 2 for relevant parameters).
[0165] Comparative Example 2
[0166] A secondary battery was assembled in the same manner as in Example 1, except that only the mixture material 2-9 (carbon material containing only secondary particles) was used as the second negative electrode active material (see Table 2 for relevant parameters).
[0167] Comparative Example 3
[0168] A secondary battery was assembled in the same manner as in Example 1, except that only the mixture material 2-10 (carbon material containing only primary particles) was used as the second negative electrode active material (see Table 2 for relevant parameters).
[0169] Table 1: First negative electrode active material
[0170]
[0171] The “ / ” in Table 1 indicates that the item does not exist.
[0172] Table 2: Second negative electrode active material
[0173]
[0174] Secondary battery performance test
[0175] Low temperature fast charging performance test
[0176] At -10°C, the batteries prepared in the examples and comparative examples were fully charged at xC and fully discharged at 1C in the range of 20%-50% SOC. After 10 cycles, the batteries were fully charged at xC and then disassembled to observe whether lithium was deposited on the surface of the negative electrode. If lithium was not deposited on the negative electrode surface, the charging rate xC was increased by 0.1C as a gradient and tested again until lithium was deposited on the negative electrode surface. The test was stopped and the charging rate (x-0.1)C at this time was the maximum charging rate of the battery.
[0177] Table 3 below shows the parameters of the negative electrode sheets of Examples 1-9 and Comparative Examples 1-3 and the secondary battery performance test results.
[0178] Table 3:
[0179]
[0180] It can be seen from Table 3 that compared with Comparative Example 1 (Dv50 of the second negative electrode active material is greater than 13), Comparative Example 2 (the second negative electrode active material only uses secondary particles) and Comparative Example 3 (the second negative electrode active material only uses primary particles), in Examples 1-9, the low-temperature fast charging performance of the secondary battery is significantly improved by arranging the second negative electrode active material to include primary particles of carbon material and secondary particles of carbon material.
[0181] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector; the negative electrode film layer comprises a lower region and an upper region, the lower region comprises a first negative electrode active material, and the upper region comprises a second negative electrode active material; in, The second negative electrode active material includes both primary particles of carbon material and secondary particles of carbon material, and the volume distribution particle size D of the second negative electrode active material is V 50 is less than or equal to 13μm.
2. The secondary battery according to claim 1, characterized in that: The volume distribution particle size D of the second negative electrode active material V 50 is 8μm~13μm.
3. The secondary battery according to claim 1 or 2, characterized in that: The volume distribution particle size D of the primary particles of the carbon material V 50 is smaller than the volume distribution particle size D of the carbon material of the secondary particles V 50; Optionally, the volume distribution particle size D of the carbon material of the primary particles is V 50 is 3.5 μm to 6 μm, and more preferably 3.5 μm to 5.0 μm; Optionally, the volume distribution particle size D of the carbon material of the secondary particles is V 50 is 10.0 μm to 14.0 μm, and more preferably 10.0 μm to 13.5 μm.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The powder OI value of the carbon material of the primary particles is greater than the powder OI value of the carbon material of the secondary particles; Optionally, the powder OI value of the carbon material of the primary particles is 3 to 6; Optionally, the powder OI value of the carbon material of the secondary particles is 2 to 5.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The specific surface area of the carbon material of the primary particles is greater than the specific surface area of the carbon material of the secondary particles; Optionally, the specific surface area of the carbon material of the primary particles is 2.0 m 2 / g to 3.5m 2 / g, 2.0m can be selected 2 / g to 3.2m 2 / g; Optionally, the specific surface area of the carbon material of the secondary particles is 0.6 m 2 / g to 1.5m 2 / g, optional 0.6m 2 / g to 1.2m 2 / g.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The carbon material of the primary particles further satisfies at least one of the following (1) to (6): (1) Volume distribution particle size D of the primary particles of the carbon material V 10: 1.0 μm to 3.0 μm; (2) Volume distribution particle size D of the primary particles of the carbon material V 90 is 9μm to 12μm; (3) The particle size distribution of the carbon material of the primary particles (D V 90-D V 10) / D V 50 is 1.1 to 1.8; (4) The tap density of the carbon material of the primary particles is 0.8 g / cm 3 Up to 1.1g / cm 3 ; (5) The powder compaction density of the carbon material of the primary particles at 20000N is 1.35g / cm 3 Up to 1.55g / cm 3 ; (6) The carbon material of the primary particles has a graphitization degree of 90% to 93%.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: The carbon material of the secondary particles further satisfies at least one of the following (1) to (6): (1) Volume distribution particle size D of the secondary particles of carbon material V 10: 4.5 μm to 8.0 μm; (2) Volume distribution particle size D of the secondary particles of carbon material V 90: 18 μm to 24 μm; (3) The particle size distribution of the carbon material of the secondary particles (D V 90-D V 10) / D V 50: 0.9 to 1.3; (4) The tap density of the carbon material of the secondary particles is 0.9 g / cm 3 Up to 1.2g / cm 3 ; (5) The powder compaction density of the carbon material of the secondary particles at 20000N is 1.55g / cm 3 Up to 1.70g / cm 3 ; (6) The degree of graphitization of the carbon material of the secondary particles is 92% to 95%.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: Based on the total mass of the second negative electrode active material, the mass proportion of the carbon material of the primary particles is less than the mass proportion of the carbon material of the secondary particles; Optionally, based on the total mass of the second negative electrode active material, the mass proportion of the carbon material of the primary particles is 20% to 40%; Optionally, based on the total mass of the second negative electrode active material, the mass proportion of the carbon material in the secondary particles is 60% to 80%.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The carbon material of the primary particles and / or the carbon material of the secondary particles is artificial graphite.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The first negative electrode active material includes artificial graphite and / or natural graphite; Optionally, the first negative electrode active material includes both artificial graphite and natural graphite.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The first negative electrode active material comprises natural graphite, and the volume distribution particle size D of the natural graphite is V 50 is 9μm to 20μm.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: The first negative electrode active material includes secondary particles of artificial graphite.
13. The secondary battery according to any one of claims 1 to 12, characterized in that: The first negative electrode active material comprises artificial graphite, and the volume distribution particle size D of the artificial graphite is V 50 is 12μm to 17μm, and can be optionally 13μm to 16μm.
14. The secondary battery according to any one of claims 1 to 13, characterized in that: The first negative electrode active material includes natural graphite, and the natural graphite satisfies at least one of the following (1) to (6): (1) Volume distribution particle size D of the natural graphite V 10: 5.0 μm to 12.0 μm; (2) Volume distribution particle size D of the natural graphite V 90: 20 μm to 30 μm; (3) The particle size distribution of the natural graphite (D V 90-D V 10) / D V 50: 0.9 to 1.3; (4) The tap density of the natural graphite is 0.9 g / cm 3 Up to 1.2g / cm 3 ; (5) The powder compaction density of the natural graphite at 20000N is 1.60g / cm 3 Up to 1.90g / cm 3 ; (6) The degree of graphitization of the natural graphite is 96% to 98%.
15. The secondary battery according to any one of claims 1 to 14, characterized in that: The first negative electrode active material includes artificial graphite, and the artificial graphite satisfies at least one of the following (1) to (6): (1) Volume distribution particle size D of the artificial graphite V 10: 4 μm to 8 μm; (2) Volume distribution particle size D of the artificial graphite V 90: 25 μm to 40 μm; (3) The particle size distribution of the artificial graphite (D V 90-D V 10) / D V 50 is 1.0 to 1.4; (4) The tap density of the artificial graphite is 0.95 g / cm 3 Up to 1.25g / cm 3 ; (5) The powder compaction density of the artificial graphite at 20000N is 1.70g / cm 3 Up to 1.90g / cm 3 ; (6) The degree of graphitization of the artificial graphite is 93% to 95%.
16. An electrical device comprising the secondary battery according to any one of claims 1 to 15.
Citation Information
Patent Citations
Negative active material for rechargeable lithium battery and rechargeable lithium battery including same
CN109478647A
Negative plate and energy storage device
CN111540883A
Quick-charging type high-energy-density lithium ion battery
CN111600066A
Secondary batteries, their preparation methods, and devices containing such secondary batteries
CN113875047B
Negative electrode and rechargeable lithium battery including same
CN115692597A